Analyzing the Economic Impact of Capital Structure as a Mediator on Firm Value - Fentinia Rika Karlina; Umi Nadhiroh (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the effect of Return on Assets (ROA) and Return on Equity (ROE) on firm value, with the Debt to Asset Ratio (DAR) as a mediating variable. Firm value is measured using two indicators, namely Price to Book Value (PBV) and Tobin’s Q. The study was conducted on companies in the industrial and mining sectors listed on the Indonesia Stock Exchange (IDX) over a four-year observation period. The approach used is quantitative explanatory research, employing the Partial Least Square (PLS) analysis technique to test both direct and indirect relationships among variables. The results indicate that ROA and ROE have no significant effect on firm value (both PBV and Tobin’s Q). However, ROA has a significant negative effect on DAR, suggesting that companies with higher profitability levels tend to rely less on debt-based financing. Meanwhile, DAR shows no significant effect on firm value, whether measured by PBV or Tobin’s Q, implying that capital structure does not serve as a mediating variable in the relationship between profitability and firm value. Thus, the increase in firm value cannot be explained through the mechanism of capital structure in industrial and mining sector companies in Indonesia. The implications of this study suggest that internal fundamental factors such as profitability and capital structure are not yet the main determinants shaping firm value. External factors such as commodity price fluctuations, macroeconomic conditions, and investor perceptions of financial risk are presumed to have a greater influence on firm value. Future research is recommended to include additional variables such as firm size, growth opportunity, and good corporate governance to enhance understanding of the dynamics determining firm value.